Association of Perforator Stroke After Basilar Artery Stenting With Negative Remodeling. Issue 3 (March 2019) - Ma, Ning; Xu, Ziqi; Lyu, Jinhao; Li, Mingyao; Hou, Zhikai; Liu, Yifan; Yang, Ming; Mo, Dapeng; Gao, Feng; Song, Ligang; Sun, Xuan; Liu, Lian; et al.
Abstract : Background and Purpose—: We try to evaluate whether plaque features and perforator stroke after intracranial stenting is associated with the arterial remodeling patterns in patients with severe basilar artery stenosis. Methods—: We studied patients with symptomatic intracranial arterial stenosis who underwent high-resolution magnetic resonance imaging from September 2014 to January 2017. Among them, patients with basilar artery stenosis underwent angioplasty and stenting were recruited. Arterial remodeling patterns were divided into negative or nonnegative remodeling. Plaque features were investigated by high-resolution magnetic resonance imaging, which includes plaque distribution, intraplaque hemorrhage, calcification, as well as enhancement patterns. Incidence of perforator strokes after intracranial stenting was recorded. Plaque features and incidence of poststenting perforator stroke were compared between negative and nonnegative remodeling. Results—: Two hundred ninety-eight consecutive patients were enrolled. Among them, 30 patients fulfilled the inclusion criteria. There were 11 patients (36.7%) with negative remodeling and 19 (63.3%) with nonnegative remodeling. Twenty-six patients (86.7%) had diffuse distribution, 5 patients (16.7%) had intraplaque hemorrhage, 2 patients (6.7%) had calcification, and 17 patients (65.4%) had enhancement. Three patients had perforator stroke after stenting. Plaque features were similar between negative and nonnegative remodeling groups. Patients with negative remodeling were more likely to have perforator stroke after stenting comparing with patients with nonnegative remodeling (27.3% versus 0%, P =0.041). Conclusions—: Perforator stroke after basilar artery stenting may be related to negative remodeling on high-resolution magnetic resonance imaging. The finding needs to be confirmed in future studies. Clinical Trial Registration—: URL:https://www.clinicaltrials.gov . Unique identifier: NCT02705599. Abstract : Supplemental Digital Content is available in the text.